Metabolic engineering of Clostridium acetobutylicum and product extension - Omorotionmwan, Bunmi Busola (2020)
The limited abundance of fossil fuels and its harmful effects on the environment has led to the increased global interest in more environmentally friendly sources of chemicals and fuels. The solventogenic Clostridium acetobutylicum represents a model organism for solvent production in this genus and in the so-called ABE fermentation produces acetone, butanol and ethanol in a 3:6:1 ratio.